Communication Management of Wildlife Conflict Resolution in Islamic Perspective in BBKSDA Riau - Andi Kardian Riva’i; Mailin Mailin; Rusli Rusli; Arnan Lubis; Tisi Maulidia Putri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the performance of handling wildlife conflicts; seek solutions for handling conflicts that have occurred; efforts to prevent and manage conflict victims from the community or wildlife. The method used is a naturalistic approach, the subject of this study relates to officers involved in assisting wildlife conflict resolution at the Natural Resources Conservation Center (BBKSDA) Riau Province. The results of the study show that some planning and development of wildlife conflict resolution messages have been carried out, such as socialization and assistance to the Wildlife Rescue Unit (WRU) in collaboration with land owners and managers, Government Apparatus, TNI/Polri. The aspect of communication management is a strategic analysis in building collaboration and awareness of the community, government, industry, and every citizen who has a collective awareness in order to save a harmonious, quality, and sustainable environmental condition. In the context of the Islamic religious perspective, one of the goals of communication is to spread the value of goodness, which has been regulated in the Quran the rules of how humans regulate their relationships with humans and with the natural surroundings.